Gas Store Data Analysis Using ERD Method and Constitutional Data Warehouse Model - Fahmi Risaldi; Vany Terisia; Shevty Arbekti Arman; Diana Yusuf (Journal of Computer Science Advancements, 2023)
A data warehouse is a data storage system that plays a crucial role in business analysis. It collects, integrates, and stores data from multiple sources in a structured format, providing holistic insight into organizational performance. Entity-Relationship Model (ERD) is a visual tool for designing database structures. It uses entities to represent real-world objects and the relationships between them. ERD helps plan an efficient and coherent database design. A conceptual model is an abstract visual representation of information structures and relationships within a domain. It covers key concepts and business rules, assisting in building a solid foundation of understanding before technical designing begins. All three are interrelated in the development of successful information systems. Data warehouses use conceptual models to direct effective data storage design, while ERD helps describe the entities and relationships to be stored in the data warehouse. The combination of all three enables organizations to design, develop, and maintain adequate information systems, based on a deep understanding of data and its relationships. This results in better decision making, more efficient innovation, and optimal utilization of resources. The purpose of this study is to produce optimal data using the ERD method. The main objective is to explain how much data in an information system in the Company and how data management is crucial for effective decision making.